IL‐1β associations with posttraumatic epilepsy development: A genetics and biomarker cohort study - Diamond, Matthew L.; Ritter, Anne C.; Failla, Michelle D.; Boles, Jennifer A.; Conley, Yvette P.; Kochanek, Patrick M.; Wagner, Amy K. (Epilepsia (Copenhagen), 2014)
Summary Objective Posttraumatic epilepsy (PTE) is a significant complication following traumatic brain injury (TBI), yet the role of genetic variation in modulating PTE onset is unclear. We hypothesized that TBI‐induced inflammation likely contributes to seizure development. We assessed whether genetic variation in the interleukin‐1beta (IL‐1β) gene, IL‐1β levels in cerebrospinal fluid (CSF) and serum, and CSF/serum IL‐1β ratios would predict PTE development post‐TBI. Methods We investigated PTE development in 256 Caucasian adults with moderate‐to‐severe TBI. IL‐1β tagging and functional single nucleotide polymorphisms (SNPs) were genotyped. Genetic variance and PTE development were assessed. Serum and CSF IL‐1β levels were collected from a subset of subjects (n = 59) during the first week postinjury and evaluated for their associations with IL‐1β gene variants, and also PTE. Temporally matched CSF/serum IL‐1β ratios were also generated to reflect the relative contribution of serum IL‐1β to CSF IL‐1β. Results Multivariate analysis showed that higher CSF/serum IL‐1β ratios were associated with increased risk for PTE over time (p = 0.008). Multivariate analysis for rs1143634 revealed an association between the CT genotype and increased PTE risk over time (p = 0.005). The CT genotype group also had lower serum IL‐1β levels (p = 0.014) and higher IL‐1β CSF/serum ratios (p = 0.093). Significance This is the first report implicating IL‐1β gene variability in PTE risk and linking (1) IL‐1β gene variation with serum IL‐1β levels observed after TBI and (2) IL‐1β ratios with PTE risk. Given these findings, we propose that genetic and IL‐1β ratio associations with PTE may be attributable to biologic variability with blood–brain barrier integrity during TBI recovery. These results provide a rationale for further studies (1) validating the impact of genetic variability on IL‐1β production after TBI, (2) assessing genetically mediated signaling mechanisms that contribute to IL‐1β CSF/serum associations with PTE, and (3) evaluating targeted IL‐1β therapies that reduce PTE. A PowerPoint slide summarizing this article is available for download in the Supporting Information section here.